Validation of the hypothesis on the protective role of functional beverages in mitigating the adverse health effects of digital technologies - Tultabayev, Mukhtar; Zhumanova, Umyt; Tultabayeva, Tamara; Shoman, Aruzhan (Frontiers in Nutrition, 2025)
The widespread adoption of digital technologies (DT) and artificial intelligence (AI) has led to the emergence of digital stress (DS), characterized by anxiety, cognitive overload, visual fatigue, and emotional exhaustion. This study aims to validate the objective that functional beverages (FB), containing vitamins, minerals, probiotics, adaptogens, and antioxidants, can mitigate the adverse health effects of DS. The outlook of this objective includes the following: (1) assessing the protective potential of FB in reducing stress, enhancing cognitive function, protecting vision, normalizing sleep, and preventing the hereditary transmission of stress; (2) developing recommendations for next-generation FB with a focus on synergistic formulations and personalized approaches; and (3) justifying the use of advanced delivery technologies to enhance component bioavailability. A systematic review of empirical data confirmed the protective role of FB, demonstrating their effectiveness in alleviating DS consequences. Strategies for FB development were proposed, including the use of nanoemulsions, liposomes, and AI models for personalization, ensuring scalability and practical implementation of the hypothesisPROSPERO registrationCRD420251077775.